Synthesis of Bio-Silver Nanoparticles using Leaf Extract of Cymbopogon nardus and Examination of Their Physical and Anti-Bacterial Properties - Synodalia C. Wattimena; Veince B. Silahooy; Philipus J. Patty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
The production of silver nanoparticles using biological methods has become the preferred choice of experts over chemical and physical methods because it is cost-effective, rapid, requires minimal energy, and is environmentally friendly. In this study, antibacterial activities of bio-silver nanoparticles synthesized using leaf extract of Cymbopogon nardus against Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Escherichia coli (E. coli) were assessed. Using TEM it was found that most of the nanoparticles are spherical, and their diameters vary from 7.0 nm to 31.0 nm with the mean diameter calculated to be 15.7 ± 4.60 nm. The UV-VIS spectrum shows 435 nm as the wavelength of localized surface plasmon resonance while the FTIR spectrum indicates the presence of the extract on the surface of the particles, suggesting the action of extracts as the reducing as well as capping agents. Antibacterial assessment was done using both diffusion disc and spectrophotometric methods, and the results show that the silver nanoparticles can inhibit the growth of both gram-positive (S. aureus) and gram-negative (E. coli) bacteria.